Improve Students Activeness With Lesson Study Based Debate Model Integrated Numbered Heads Together Model - Irawan, Yuliandy Rige; Haryono, Agung; Rokhmani, Lisa (Unversitas Negeri Malang, 2017)
Based on preliminary observation in Public Senior High School 1 Tumpang eleventh social three class, known that the problem faced by the school mentioned is the learning process applied by the teacher is mainly lecturing and giving an assignment, also the lesson study has not been applied yet. What is more, students still tend to pay less attention or less observant to Economics subject and some of the students were less active or passive in giving an opinion in class so a proper, interesting and fun learning is necessary, that isÂ Lesson Study Based Debate Model integrated with Numbered Head Together (NHT). This study aims to describe the implementation of lesson study based debate model combined with numbered head together model (NHT) to enhance student activeness on economics subject (study case of eleventh social three students of Public Senior High School 1 Tumpang 2015/2016 academic year). The type of this research is classroom action research through lesson study. This research was conducted in two cycles. The subject of this research is eleventh social three students of Public Senior High School 1 Tumpang with the total 30 students that consist of 13 males and 17 females 2015/2016 academic year. The data used is lesson study based debate model integrated with numbered head together model (NHT) from analyzing learning implementation plan and observation page, and studentsâ€™ activeness from observation page. The instruments are observation page, field notes, documentation, and interview.Â Keywords: Activeness, Debate and Numbered Head Together (NHT)